HISTORIA DEL ARTE MEXICANO - Salvat, Juan (dirección) (1986)
CONTENIDO: V. 1, 2, 3, 4, ARTE PREHISPANICO. -- V. 5, 6, 7, 8 ARTE COLONIAL. -- V. 9, 10, 11, 12 ARTE DEL SIGLO XIX. -- V. 13, 14 15 ARTE CONTEMPORANEO